Born broken : an adoptive journey - Berry, Kristin (New Leaf Press, 2017)
"The story began like a dream. A child is born with all the possibilities of a bright future. Nearby, a loving family waits for the son they have always dreamed of. When they become a family, little league, playdates, birthday parties and college scholarships all seem within the grasp of this all-American family. But when the fairy tale ended. The family realizes their precious child is struggling with the most basic developmental milestones, and they vow to love him more. However, the truth of their son's condition is something that even the strongest family could not undo. His brain has been damaged by alcohol before he was even born. Fetal Alcohol Spectrum Disorder is the leading cause of birth defects and developmental disabilities in the United States... and there is no cure. One family's powerful story of faith began. The fight to advocate for their son in a world that did not understand left this family feeling exhausted and hopeless. The isolation of their reality almost destroyed their marriage and their family, until they found the strength in a community they never knew existed. They found families that were struggling too. They stepped out of isolation and together they found faith and hope once again."--Page [4] of cover.